Editor’s Foreword - Radaev, Vadim (Journal of Economic Sociology, 2022)
Dear colleagues, The geopolitical positions of Russia and the general situation in the world keep on deteriorating. Predictions for the future are becoming increasingly gloomy. Let us hope that worst of these predictions will never come true.